The Virtuous Cycle of Property - Fabbri, Marco; Dari-Mattiacci, Giuseppe (The Review of Economics and Statistics, 2021)
This paper shows that formalizing private property rights has a positive effect on the propensity to respect the property of others. We study a recent large-scale land tenure reform in West Africa that was the first of its kind to be implemented as a randomized control trial. Results of a modified dictator game show that the formalization of private property rights reduced an individual's willingness to take from others' endowment. We used additional experimental measures and postexperimental survey data to rule out alternative explanations for the observed behavior that do not imply a change in preferences.